Impact Prefabrication Technology (Pre Engineering) and Equipments on Profitability in Construction Industry: Exploring the impact of pre-engineering and prefabrication technology on profitability in the construction industry (Journal of Advances and Scholarly Researches in Allied Education, 2023)
The world is technologically progressing quicker than ever. The factors that governdevelopment have altered significantly recently and will continue to do so in the future. The set ofcatalytic forces that are accelerating the pace of social change around the world includes a rapid rise ineducation levels, high rates of technological innovations and applications, ever faster and lessexpensive communication that breaks down physical and social barriers both within and betweennations, increased availability and easier access to information, and the further opening up of globalmarkets.It has been demonstrated that using conventional building techniques will not help you do this. The maintenets of fast track construction have been mechanisation and parallel working. Fast-tracking the taskswithout prior preparation will almost always lead to significant errors and re-working. Therefore, anumber of factors, including technology, planning, information, education, and employable skills, will becrucially important in determining how growth will go in the future.One of the finest uses of fast track construction is preengineering. The pre-engineered building ideauses predesigned and prefabricated steel building systems.The current building approach demands thegreatest aesthetic appearance, high quality and speedy construction, as well as a cost-effective andunique touch. Pre-engineered steel structures are one alternative construction method to consider. PreEngineered Building (PEB) concept introduction in structure design in recent years has aided in designoptimisation. This study goes into great depth about the use of pre-engineering in quick construction.